Integrasi Konsep Geometri dan Etnomatematika : Pemanfaatan Ketupat Sebagai Media Kontekstual Berbasis Kearifan Lokal dalam Pembelajaran Matematika - Ima Rosila; Umi Mahmudah (Lembaga Pengembangan Kinerja Dosen, 2025)
mathematical instruction often lacks relevance to students’ real-life contexts, necessitating more meaningful and contextualized approaches. This study aims to integrate geometric concepts and ethnomathematics through the utilization of ketupat a traditional Indonesian cultural artifact as a culturally grounded instructional medium. A descriptive qualitative method was employed, using literature review and contextual observation of the geometric structure of ketupat. The findings reveal that ketupat encompasses geometric elements such as symmetry, three-dimensional forms, woven patterns, and calculations of volume and surface area. Moreover, ketupat holds significant symbolic meaning within Indonesian culture, making it a relevant bridge between mathematical concepts and local values. The study concludes that using ketupat as a contextual medium enhances students’ conceptual understanding of geometry and strengthens the integration of cultural values within mathematics education.